Introduction to Mindfulness: Evidence-Based Medicine Lecture and Active Session - Magdalena Pasarica; Ernestine Lee; Michael Lee (Association of American Medical Colleges, 2016)
Abstract Introduction There is a growing body of evidence regarding the effectiveness of mindfulness practices and the benefits for the resilience of patients and medical professionals. Thus, there is a need to educate medical students in this technique and its benefits, but there are no readily available resources that emphasize the current evidence. We developed an introductory session for the mindfulness technique as an evidenced-based medicine lecture combined with an active mindfulness exercise. Methods This session consisted of a PowerPoint lecture overview of mindfulness, a topic unknown to most students, with an emphasis on evidence-based facts, as well as an active practical mindfulness exercise. The effectiveness of the lecture was assessed using a survey instrument, which was designed to assess the learners' knowledge and interest in learning and using mindfulness (before and after the session) and their interest in integrating mindfulness into the medical school curriculum. The survey contained six multiple-choice questions. Participation was voluntary and anonymous, with the use of Turning Point technology (an audience response system). Results The session was administered to and evaluated by first- and second-year medical students with no prior instruction in mindfulness. The session was held by a physician who uses mindfulness in the clinic. After the session, 90% of students were interested in learning more about mindfulness, and the majority were interested in having mindfulness integrated into the medical curriculum. Discussion The results suggest the session can be effectively used as is in other medical teaching institutions to introduce students to mindfulness and to assess students' perception of knowledge in the area and their interest in both having more comprehensive training on the subject and practicing mindfulness in medical care.